2013
DOI: 10.1152/ajprenal.00563.2012
|View full text |Cite
|
Sign up to set email alerts
|

Gain-of-function variant of the human epithelial sodium channel

Abstract: ϩ channel (ENaC) mutations are associated with several human disorders, underscoring the importance of these channels in human health. Recent human genome sequencing projects have revealed a large number of ENaC gene variations, several of which have been found in individuals with salt-sensitive hypertension, cystic fibrosis, and other disorders. However, the functional consequences of most variants are unknown. In this study, we used the Xenopus oocyte expression system to examine the functional properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 45 publications
1
31
0
Order By: Relevance
“…Site-directed mutagenesis studies using human ENaC subunits showed that mutation of these residues to alanine also leads to a decrease in sodium feedback inhibition that controls channel open probability (P o ) (Edelheit et al, 2014, 2011). A human γ subunit variant in the palm domain (L511Q) is associated with an increase in channel open probability (Chen et al, 2013). …”
Section: Conserved Sequence Motifs and Their Functionsmentioning
confidence: 99%
“…Site-directed mutagenesis studies using human ENaC subunits showed that mutation of these residues to alanine also leads to a decrease in sodium feedback inhibition that controls channel open probability (P o ) (Edelheit et al, 2014, 2011). A human γ subunit variant in the palm domain (L511Q) is associated with an increase in channel open probability (Chen et al, 2013). …”
Section: Conserved Sequence Motifs and Their Functionsmentioning
confidence: 99%
“…4 Mechanisms by which these hormones regulate renal ENaCs have been the focus of numerous reviews. 2, 3, 9, 2629 Aldosterone increases expression of the α subunit as well as many other proteins, including the serum and glucocorticoid regulated kinase (SGK1), and the adaptors glucocorticoid-induced leucine zipper 1 (GILZ1) and connector enhancer of kinase suppressor of Ras isoform 3, which enhance surface expression of channels. 2, 3035 …”
Section: Expression and Regulation Of Enac In The Distal Nephronmentioning
confidence: 99%
“…13 The regulated reabsorption of filtered Na + by the nephron has a key role in the regulation of extracellular fluid volume and blood pressure. 4 The role of these channels in the control of blood pressure is highlighted by gain-of-function mutations (Liddle syndrome) and loss-of-function mutations (pseudohypoaldosteronism type I) that are associated with increases or decreases in blood pressure, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2). Previous studies suggest that channels with a high intrinsic P o are less sensitive to extracellular Na ϩ (9,24,31,45) and stimulation by mechanical forces (7,8). As shown in Fig.…”
Section: Resultsmentioning
confidence: 83%